Hi Maria;

Slope is change-of-y divided by change-of-x.

m=(y-y

(-3, 4) and (2, 1)

m=(4-1)/(-3-2)

m=3/-5

m=-3/5

Point-slope formula is...

y-y

We will apply one point. Let's begin with (-3, 4)...

y-4=(-3/5)(x--3)

y-4=(-3/5)(x+3)

Second point, (2, 1)...

y-1=(-3/5)(x-2)

m=(y-y

_{1})/(x-x_{1})(-3, 4) and (2, 1)

m=(4-1)/(-3-2)

m=3/-5

m=-3/5

Point-slope formula is...

y-y

_{1}=m(x-x_{1})We will apply one point. Let's begin with (-3, 4)...

y-4=(-3/5)(x--3)

y-4=(-3/5)(x+3)

**B. y - 4 = - 3/5(x + 3)**Second point, (2, 1)...

y-1=(-3/5)(x-2)

**A. y - 1 = - 3/5(x - 2)**